Capturing information contagion in a stress-testing framework - Kartik Anand; Céline Gauthier; Prasanna S. Gai; Moez Souissi (Deutsche Bundesbank, 2016)
We develop an operational model of information contagion and show how it may be integrated into a mainstream, top-down, stress-testing framework to quantify systemic risk. The key transmission mechanism is a two-way interaction between the beliefs of secondary market investors and the coordination failure between the creditors of financial institutions. Pessimism about macroeconomic fundamentals triggers creditor runs, but also influences the fire sale discount applied to illiquid assets by secondary market investors. This hampers a troubled bank's recourse to liquidity and increases the incidence of bank runs, potentially unleashing a wave of investor pessimism that can drive otherwise solvent banks into illiquidity. We quantify this contagion channel in the context of the Bank of Canada's model of the Canadian banking system and a stress-test scenario used by the IMF during its 2013 evaluation of the Canadian financial sector.
Keywords: G01; G21; G28; C72; E58; 330; liquidity risk; contagion; stress testing; global games